Goods Storage Rental Application (YourStorage) Using the React Native Framework - Hardjanto, Farhan Rifanto; Nugroho, Aldi; Hidayat, Faridz; Zulfikar, Muhammad Taufiq (Engineering, MAthematics and Computer Science Journal (EMACS), 2024)
The increase in online business today with quite high transactions means that business actors who sell their merchandise through marketplaces need temporary storage space that does not have a place to store goods. Based on this, the aim of this research is to build a goods storage rental application to make it easier for business actors to rent storage space online with flexible time periods. This type of research is quantitative research where the system development method uses SCRUM and the software architecture used is service-oriented (Microservice). The results of this research are in the form of an Android-based mobile application and as many as 75% of business respondents feel that the â€œYourStorageâ€ application can help, 68.75% (22) of respondents stated that the application could help in controlling where goods are stored and 71.87% (23) of respondents stated that the application could make it easier to store goods according to required size